Dosage Compensation of X-Linked Muller Element F Genes but Not X-Linked Transgenes in the Australian Sheep Blowfly. - Rebecca J Linger; Esther J Belikoff; Maxwell J Scott (PLoS ONE, 2015)
In most animals that have X and Y sex chromosomes, chromosome-wide mechanisms are used to balance X-linked gene expression in males and females. In the fly Drosophila melanogaster, the dosage compensation mechanism also generally extends to X-linked transgenes. Over 70 transgenic lines of the Australian sheep blowfly Lucilia cuprina have been made as part of an effort to develop male-only strains for a genetic control program of this major pest of sheep. All lines carry a constitutively expressed fluorescent protein marker gene. In all 12 X-linked lines, female larvae show brighter fluorescence than male larvae, suggesting the marker gene is not dosage compensated. This has been confirmed by quantitative RT-PCR for selected lines. To determine if endogenous X-linked genes are dosage compensated, we isolated 8 genes that are orthologs of genes that are on the fourth chromosome in D. melanogaster. Recent evidence suggests that the D. melanogaster fourth chromosome, or Muller element F, is the ancestral X chromosome in Diptera that has reverted to an autosome in Drosophila species. We show by quantitative PCR of male and female DNA that 6 of the 8 linkage group F genes reside on the X chromosome in L. cuprina. The other two Muller element F genes were found to be autosomal in L. cuprina, whereas two Muller element B genes were found on the same region of the X chromosome as the L. cuprina orthologs of the D. melanogaster Ephrin and gawky genes. We find that the L. cuprina X chromosome genes are equally expressed in males and females (i.e., fully dosage compensated). Thus, unlike in Drosophila, it appears that the Lucilia dosage compensation system is specific for genes endogenous to the X chromosome and cannot be co-opted by recently arrived transgenes.